LESBIAN MARGINALIZATION CONSTRUCTION IN SURABAYA PAGI DAILY NEWSPAPER - Nadya Afdholy; Eggy Fajar Andalas; Dody Irawan; Arif Fatchur Rochmaniyah (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2019)
Power not only operates through formal channels, law, and state institutions but also operates through a series of discourse to define something or a group as incorrect or bad. This study aims to describe the process of paralleling the construction of the Surabaya Pagi newspaper by using a critical analysis of Theo Van Leeuwen's model. This study uses a descriptive qualitative method to see the formation of an opinion on a newspaper text entitled